Development of Dual-Targeted Mixed Micelles Loaded with Celastrol and Evaluation on Triple-Negative Breast Cancer Therapy - Siying Huang; Simeng Xiao; Xuehao Li; Ranran Tao; Zhangwei Yang; Ziwei Gao; Junjie Hu; Yan Meng; Guohua Zheng; Xinyan Chen (MDPI AG, 2024)
Considering that the precise delivery of Celastrol (Cst) into mitochondria to induce mitochondrial dysfunction may be a potential approach to improve the therapeutic outcomes of Cst on TNBC, a novel tumor mitochondria dual-targeted mixed-micelle nano-system was fabricated via self-synthesized triphenylphosphonium-modified cholesterol (TPP-Chol) and hyaluronic acid (HA)-modified cholesterol (HA-Chol). The Cst-loaded mixed micelles (Cst@HA/TPP-M) exhibited the characteristics of a small particle size, negative surface potential, high drug loading of up to 22.8%, and sustained drug release behavior. Compared to Cst-loaded micelles assembled only by TPP-Chol (Cst@TPP-M), Cst@HA/TPP-M decreased the hemolysis rate and upgraded the in vivo stability and safety. In addition, a series of cell experiments using the triple-negative breast cancer cell line MDA-MB-231 as a cell model proved that Cst@HA/TPP-M effectively increased the cellular uptake of the drug through CD44-receptors-mediated endocytosis, and the uptake amount was three times that of the free Cst group. The confocal results demonstrated successful endo-lysosomal escape and effective mitochondrial transport triggered by the charge converse of Cst@HA/TPP-M after HA degradation in endo-lysosomes. Compared to the free Cst group, Cst@HA/TPP-M significantly elevated the ROS levels, reduced the mitochondrial membrane potential, and promoted tumor cell apoptosis, showing a better induction effect on mitochondrial dysfunction. In vivo imaging and antitumor experiments based on MDA-MB-231-tumor-bearing nude mice showed that Cst@HA/TPP-M facilitated drug enrichment at the tumor site, attenuated drug systemic distribution, and polished up the antitumor efficacy of Cst compared with free Cst. In general, as a target drug delivery system, mixed micelles co-constructed by TPP-Chol and HA-Chol might provide a promising strategy to ameliorate the therapeutic outcomes of Cst on TNBC.